Patronage, Leadership, and Conflict in the Republic: the Relationship of Caesar and Octavian with Veterans (64 BC-27 BC) - de Oliveira, Ayla Fernanda (Romanitas - Revista de Estudos Grecolatinos, 2025)
In this article, we aim to analyze the role of veterans between 64 and 27 BC, in the final decades of the Republic, as a support group for Julius Caesar and Octavian. During this period, the veterans emerged as a significant force, quickly co-opted by these leaders, who saw in them a resource to challenge senatorial politics. In exchange for their support, the veterans demanded material benefits, consolidating a patronage–client relationship. This bond not only characterized their actions but also contributed to the profound social transformations that marked the Republican crisis.
Keywords: Late Republic; Conflict; Veterans; Julius Caesar; Octavian